A Desert Feast : Celebrating Tucson's Culinary Heritage - Niethammer, Carolyn J. (Southwest Center series., 2020)
"This book offers a food pilgrimage, where stories and recipes demonstrate why the desert city of Tucson became American's first UNESCO City of Gastronomy. You'll meet the farmers, small-scale food entrepreneurs, and chefs who are dedicated to making Tucson taste like nowhere else"--